2023
DOI: 10.1002/bit.28467
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli BL21 (DE3) for high‐yield production of germacrene A, a precursor of β‐elemene via combinatorial metabolic engineering strategies

Abstract: Abstractβ‐elemene is one of the most commonly used antineoplastic drugs in cancer treatment. As a plant‐derived natural chemical, biologically engineering microorganisms to produce germacrene A to be converted to β‐elemene harbors great expectations since chemical synthesis and plant isolation methods come with their production deficiencies. In this study, we report the design of an Escherichia coli cell factory for the de novo production of germacrene A to be converted to β‐elemene from a simple carbon source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Hence, we established an exogenous lycopene production platform by expressing the lycopene gene cluster crtEBI from C. glutamicum ATCC 13032 in E. coli BL21 (DE3). , The resulting strain LYC-1, while overexpressing the efficient MVA pathway, produced 13.61 mg/L of lycopene after 72 h shake-flask fermentation (Figure A, B). Although an MVA pathway was introduced, lycopene production did not increase much.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we established an exogenous lycopene production platform by expressing the lycopene gene cluster crtEBI from C. glutamicum ATCC 13032 in E. coli BL21 (DE3). , The resulting strain LYC-1, while overexpressing the efficient MVA pathway, produced 13.61 mg/L of lycopene after 72 h shake-flask fermentation (Figure A, B). Although an MVA pathway was introduced, lycopene production did not increase much.…”
Section: Resultsmentioning
confidence: 99%
“…coli (4 L bioreactor). The substitution from Y to N in the 305th residue shortened the hydrogen bond between the residues and the ligand, thereby reducing the binding affinity between the receptor and ligand …”
Section: Application Of Site-directed Mutagenesis In Stssmentioning
confidence: 99%
“…Microbial cells in the culture medium synthesize products, which are then extracted or adsorbed by the SP, disrupting the equilibrium and promoting product release. For instance, in β-elemene biosynthesis by E. coli , strategies like efflux protein enhancement and the use of n-dodecane as an organic phase in fermentation increased the β-elemene yield to 3.52 g/L [ 64 ].…”
Section: The Advantages Of Tpf Systemsmentioning
confidence: 99%
“…However, this yield is insufficient for industrial production. Recent studies have identified efficient synthases from algae and integrated key pathway enzymes, export genes, and translational engineering to implement TPF technology in bioreactors with n-dodecane as the SP, achieving a β-elemene yield of 3.52 g/L [ 64 ]. Y. lipolytica , serving as an exceptional cell factory, has been engineered to reconstruct the endogenous mevalonate pathway and regulate lipid metabolism, resulting in a β-elemene titer of 39 g/L in a bioreactor containing an isopropyl myristate organic phase [ 78 ].…”
Section: Applications Of Tpf In Microbial Production Of Terpenesmentioning
confidence: 99%